Humming - Kim, Suk-Jun 1970- (Bloomsbury Academic, 2019)
"From a gentle and soothing voice that is personal and intimate to hums that are mystical, impersonal and maddening, this book provides an anthropology of the concept of humming through the discipline of sound studies"--
1812
Keywords: Geräusch; Philosophie; Klang; Brummen; Humming / Philosophy; Humming / Anthropological aspects; Sound (Philosophy); Voice (Philosophy)